MAINSTREAMING GERAKAN SEMPALAN STUDI KASUS PERKEMBANGAN GERAKAN MTA ( MAJILIS TAFSIR AL QURAN) DI SURAKARTA - Zaki Faddad Syarif Zain (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2019)
There are at least three things that have caused the development of MTA so far. First, through MTA resources, among others, recitation and leadership of this movement has a role in recruiting members by providing religious understanding and strong relationship interactions between leaders and followers of MTA. Another resource is the dissemination of the movement's religious messages through radio play which has a major role in recruiting followers and attracts attention to join the MTA. Third, participation through religious practices and being able to form strong solidarity with one group.